HORROR GENRE IN LITERATURE AS A MEANS FOR EXPLORING THE COLLECTIVE UNCONSCIOUS (Engrami, 2025)
The horror genre aims to evoke specific emotions (such as fear) in its audience through the literary form, connecting with the deeper layers of the collective unconscious. The purpose of this paper is to analyze and interpret the horror genre through the prism of Carl Gustav Jung's theory of the collective unconscious. Horror, as a genre in literature and film, can be viewed in the context of literary, psychiatric, psychological, and philosophical disciplines. Through a detailed analysis of classic works of this genre, such as "Dracula" and "Frankenstein", and other horror stories, the paper explores the ways in which elements of fear, horror, and the irrational act as projections of archetypal symbols and motifs, which are integral parts of the collective unconscious. The paper also discusses the influence of culture and social norms on the formation and interpretation of these archetypal elements. Additionally, the paper considers the concept and mechanism of catharsis, and the manner in which the horror genre uses language and style as means to create atmosphere and deeper emotional impact on the reader.In conclusion, it summarizes the fact that the horror genre serves not only for entertainment and inducing fear but also as a means for a deeper understanding of the complexity of human psychology and the collective unconscious. Through analysis and interpretation, the paper highlights the potential of the horror genre as a tool for exploring and understanding human nature and fears, desires, and conflicts that transcend individual differences and cultural contexts.
Keywords: horror; collective unconscious; psychiatry; literature